RET Fusion: Joining the Ranks of Targetable Molecular Drivers in NSCLC - Badi El Osta, MD (JTO Clinical and Research Reports, 2020)
The era of precision medicine has resulted in the identification of a number of genomic alterations that can be targeted with novel therapies. In lung adenocarcinomas, a histology structure that accounts for nearly 50% of all cases of lung cancer, and a number of genomic targets have been linked with effective targeted therapies. For patients with advanced-stage lung adenocarcinomas, molecular testing is now a standard part of diagnostic workup; for patients that have specific driver molecular events, targeted therapies have resulted in substantial improvement in efficacy without excessive toxicity.RET gene fusions are present in approximately 1% to 2% of NSCLC. It is emerging as a new targetable driver for this population. Despite sensitivity to platinum-based chemotherapy and conflicting small reports regarding the efficacy of immune checkpoint inhibitors, there have been limited treatment approaches for this subset of patients. Multiple nonselective RET tyrosine kinase inhibitors exhibited modest anti-RET activity with an increased off-target toxicity profile that often required dose interruption, reduction, or treatment cessation. Recently, novel selective RET inhibitors pralsetinib (BLU-667) and selpercatinib (LOXO-292) have exhibited promising clinical activity with low adverse effect profile in early clinical trials. These new agents are poised to represent a new hope for this special subgroup with unmet needs.